2019
DOI: 10.1111/echo.14364
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fetal modified myocardial performance index in early‐onset and late‐onset fetal growth restriction

Abstract: Aim To investigate the changes of modified myocardial performance index (Mod‐MPI) in early‐onset and late‐onset fetal growth restriction (FGR) cases, and its association with adverse perinatal outcome. Methods This was a prospective study on 77 early‐onset and 100 late‐onset FGR cases. Hundred normal fetuses were matched as control groups for early‐onset and late‐onset FGR groups, respectively. Mod‐MPI and vessel Doppler parameters including umbilical artery (UA), ductu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Zhang et al [24] proposed that a cut-off value of the left MPI in fetus with early-onset IUGR of 0.47 conferred a sensitivity of 60%, specificity of 80% for the adverse perinatal outcome. They did not report a cut-off value for prediction perinatal death, which is different than the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [24] proposed that a cut-off value of the left MPI in fetus with early-onset IUGR of 0.47 conferred a sensitivity of 60%, specificity of 80% for the adverse perinatal outcome. They did not report a cut-off value for prediction perinatal death, which is different than the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that increased MPI was associated with adverse pregnancy outcomes. 11 Sharma et al measured MPI in 36 FGR and 36 AGA cases. They found significantly higher MPI and IRT in the FGR cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not possible or advisable to use continuous CTG in limited-resource environments 9 . Functional cardiac assessment using echocardiography is increasingly valued because it detects subtle myocardial dysfunction during growth and can guide treatment and improve neonatal results 10 .…”
Section: Discussionmentioning
confidence: 99%